Łukasiewicz fuzzy sub-hoops - Mona Aaly Kologani; Gholam Reza Rezaei; Young Bae Jun; Rajab Ali Borzooei (Miskolc Mathematical Notes)
With the purpose of applying the Łukasiewicz fuzzy set to sub-hoop in hoops, the concept of Łukasiewicz fuzzy sub-hoop is introduced, and its properties are investigated. The relationship between fuzzy sub-hoop and Łukasiewicz fuzzy sub-hoop are discussed. Conditions for Łukasiewicz fuzzy set to be a Łukasiewicz fuzzy sub-hoop are provided, and characterizations of Łukasiewicz fuzzy sub-hoop are displayed. Conditions under which ∈qO